Climate dynamics during the penultimate glacial period recorded in a speleothem from Kanaan Cave, Lebanon (central Levant). Issue 1 (25th April 2018) - Nehme, Carole; Verheyden, Sophie; Breitenbach, Sebastian F.M.; Gillikin, David P.; Verheyden, Anouk; Cheng, Hai; Edwards, R. Lawrence; Hellstrom, John; Noble, Stephen R.; Farrant, Andrew R.; Sahy, Diana; Goovaerts, Thomas; et al.
Abstract: Little is known about terrestrial climate dynamics in the Levant during the penultimate interglacial-glacial period. To decipher the palaeoclimatic history of the Marine Oxygen Isotope Stage (MIS) 6 glacial period, a well-dated stalagmite (~194 to ~154 ka) from Kanaan Cave on the Mediterranean coast in Lebanon was analyzed for its petrography, growth history, and stable isotope geochemistry. A resolved climate record has been recovered from this precisely U–Th dated speleothem, spanning the late MIS 7 and early MIS 6 at low resolution and the mid–MIS 6 at higher resolution. The stalagmite grew discontinuously from ~194 to ~163 ka. More consistent growth and higher growth rates between ~163 and ~154 ka are most probably linked to increased water recharge and thus more humid conditions. More distinct layering in the upper part of the speleothem suggests strong seasonality from ~163 ka to ~154 ka. Short-term oxygen and carbon isotope excursions were found between ~155 and ~163 ka. The inferred Kanaan Cave humid intervals during the mid–MIS 6 follow variations of pollen records in the Mediterranean basins and correlate well with the synthetic Greenland record and East Asian summer monsoon interstadial periods, indicating short warm/wet periods similar to the Dansgaard-Oeschger events during MIS 4–3 in the eastern Mediterranean region.